The Influence of Job Satisfaction and Employee Retention on Employee Performance Mediated by Perceptions of Leadership Style - Veraningsih Sinurat; Chandra Wibowo Widhianto (Ridwan Institute, 2023)
The discussion concerning the role of human resources in company management is closely linked to the effective management of the existing human resources, enabling them to play a significant role in achieving the company's goals. To ensure the company's stability, it is essential for human resource management to make efforts in maintaining employee performance. Furthermore, companies must work diligently to develop strategies for retaining employees with high potential and the ability to positively contribute to the overall performance of the company. The objective of this study is to analyze the impact of job satisfaction and employee retention on employee performance, with the mediation of leadership style perception among employees at PT XYZ. The sample for this research comprises the entire population of employees at PT XYZ who have been with the company for a minimum of six months, totaling 150 individuals. This study employs a quantitative correlational method using Structural Equation Models (SEM). Data collection was conducted through a questionnaire distributed via Google Forms among PT XYZ employees. Data analysis for this study was performed using the SmartPLS version 4.0 software. The findings of this study reveal that, at PT XYZ, job satisfaction and employee retention do not directly impact employee performance. However, they do significantly influence employees' perceptions of leadership style, with leadership style perception being identified as the key factor influencing employee performance.